TBAB in One-pot Green Approach for the Synthesis of N-Heterocyclic Compounds: A Comprehensive Review - Sahu, Bhaktisudha; Verma, Monika; Thakur, Ajay; Bharti, Ruchi; Sharma, Renu (Current Chinese Science, 2024)
Designing innovative one-pot reactions using eco-friendly methodologies has attracted a lot of attention in drug development, organic synthesis, and material sciences due to the impressive art of mitigating the possibility of side reactions, particularly for the synthesis of Ncontaining heterocycles, which are crucial for the manufacturing and development of new drugs. These moieties have demonstrated a diversity of biological applications, such as anti-tumor, antimicrobial, antibiofilm, antioxidant, and anti-inflammatory. Due to the wide range of medicinal applications, several techniques have been reported in the literature for the synthesis of these physiologically important scaffolds, employing different homogeneous and heterogeneous catalysts. One such highly efficient catalyst is tetrabutylammonium bromide (TBAB), which has gained significant attention as an efficient metal-free homogeneous phase-transfer catalyst to facilitate a reaction when the reactants are in different phases. It is also used as a zwitterionic solvent in many organic transformations and as an effective co-catalyst for a variety of coupling reactions. In the current study, we highlighted recent developments in one-pot reactions involving TBAB as a phase-transfer catalyst or zwitterionic solvent for the efficient synthesis of various biologically promising monocyclic and bicyclic N-heterocycle scaffolds.
Keywords: green chemistry